A non-invasive, reference region-based method for quantification of cerebral blood flow and oxygen metabolism using oxygen-15 labeled gases and positron emission tomography - Hiroshi Ito; Masanobu Ibaraki; Ryo Yamakuni; Naoyuki Ukon; Shiro Ishii; Kenji Fukushima; Hitoshi Kubo; Kazuhiro Takahashi (Asia Oceania Journal of Nuclear Medicine and Biology, 2025)
Objective(s): Measurement of cerebral blood flow (CBF), cerebral blood volume (CBV), cerebral oxygen extraction fraction (OEF), and cerebral metabolic rate of oxygen (CMRO2) by positron emission tomography (PET) with oxygen-15 labeled gases is widely used for investigation into the pathophysiology of occlusive cerebrovascular disease. However, all methods for quantification of CBF, CBV, OEF, and CMRO2 by PET with oxygen-15 labeled gases require invasive arterial blood sampling. The present study developed a reference region-based method for quantification of CBF, CBV, OEF, and CMRO2 using PET and oxygen-15 labeled gases based on the steady-state method without invasive arterial blood sampling.Methods: The CBF, CBV, OEF, and CMRO2 were measured in patients with occlusive cerebrovascular disease by PET using 15O-labeled gases, C15O2, C15O, and 15O2, with the steady-state method. In the present method, the ratios of values in a brain region to the reference region for CBF, CBV, OEF, and CMRO2 were calculated without invasive arterial blood sampling.Results: Good correlations were observed for the ratios of values of the cerebral lesion to the reference brain region for CBF, CBV, OEF, and CMRO2 calculated by the present method as compared with those obtained by the steady-state method with arterial blood sampling, indicating its validity. Simulation studies showed that errors in estimated values calculated by the present method were negligibly small for both conditions of misery perfusion and matched hypoperfusion.Conclusion: A simple method for noninvasive quantification of CBF, CBV, OEF, and CMRO2 using PET and oxygen-15 labeled gases could be developed based on the steady-state method. This method can be used to investigate the pathophysiology of occlusive cerebrovascular disease.